Liberalization of China–US air transport market: Assessing the impacts of the 2004 and 2007 protocols. (January 2016) - Lei, Zheng; Yu, Man; Chen, Ruowei; O'Connell, John F.
Abstract: This paper examines China's considerations in reaching the 2004 and 2007 Air Service Agreement Protocols with the United States (US) and the impacts of such policy on the China–US market from the perspective of China. Analysis shows that the 2004 and 2007 protocols have profound impacts on the China–US market. The two protocols have been associated with phenomenal traffic growth and intensified competition. Passengers also benefit from much more choice in terms of both airlines and routing. Over time, Chinese carriers' operating performance and financial performance have gradually improved after the liberalization expressed in the protocols. However, the industry's hub-building initiatives are still seriously challenged by competing hubs in Seoul and Tokyo which have diverted substantial number of passengers moving between the China and US markets. Such issues have to be addressed in order to create a win–win outcome for both countries.